Physical activity among adolescents in Sarawak: A mixed methods approach / Rosalia Binti Saimon - Rosalia, Saimon (2013)
Understanding the factors influencing adolescent physical activity in Malaysia is critical, given the high prevalence of physical inactivity in this country. Malaysia is tenth in the world and highest among the Southeast Asian nations, scoring 61.4 percent on the inactive index. The goal of this research was to examine the psychosocial and environmental factors that influence adolescent physical activity behaviour. Conducted in Kuching, Sarawak, this research found about nine percent of adolescents met the step count recommendations (15,000 steps/day for boys and 12,000 steps/day for girls). The median step count was significantly higher in boys (median=6,556; IQR=3,923) than in girls (median=6,147; IQR=2,518) (p<0.05). A mixed methods approach was carried out to discover the underlying factors for physical inactivity. The Phase I qualitative study involved photovoice technique, focus group discussions, and in-depth interviews. Twenty adolescents and eight parents were recruited in the qualitative study. Data analysis employed constant comparison methods of the grounded theory which suggested, “feeling unsafe” when being outdoors as a central theme. The Phase I study proposed 12 factors affecting adolescent physical activity: fear of crime, traffic safety, recreation facility, accessibility, aesthetics, parental restriction, parental support, cultural barriers, peer support, perceived barriers, self-efficacy and screen time. The findings in Phase I were tested in Phase II by utilising a quantitative survey. Four hundred and forty three adolescents were recruited from four secondary schools. The mean age was 13.5 (± 0.52 years). Participants provided seven-day pedometer data and completed a self-administered questionnaire in May to July 2011. The structural equation model supported five significant predictors of physical activity (p<0.05): fear of crime (β=0.194), traffic safety (β=0.178), parental restriction (β=-0.128), peer support (β=0.196), and perceived barriers (β=-0.121). Fear of crime was interrelated with traffic safety (β=-0.254). Perceived barriers mediated the effect of fear of crime on iii physical activity. This suggests that fear of “street crime” is the major factor militating against adolescents being physically active outdoors. Parental restriction and peer support are stand-alone predictors of adolescent physical activity. The total variance explained in adolescent physical activity was 11 percent. Findings emerging from the current research suggest certain predictors of physical activity among Malaysian adolescents were different from the existing literature. First, there was a positive effect of fear of crime on physical activity. Second, this research found self-efficacy has no impact on physical activity. These findings suggest the unique needs of Malaysian adolescents should be considered while planning interventions. In conclusion, this research highlighted a recurrent finding: that psychosocial and physical environment factors were significant, and these factors were interrelated and mediated in influencing adolescent physical activity. The quantitative results provide a strong confirmation of the qualitative findings through triangulation and elaboration of the constructs and their interrelationships in the emergent theory.